Retroperitoneal abscesses: a diagnostic dilemma – case series, review of the literature and practical guide for the management of iliopsoas abscessess - Kumar, Deeksha; Byrne, Hannah; Gurung, Ganga; Airon, Nitin; Rao, Milind (International Journal of Research in Medical Sciences, 2023)
Retroperitoneal abscesses are uncommon clinical conditions which can pose a notoriously difficult diagnostic dilemma. This paper focuses on the management of secondary iliopsoas abscesses (IPA). We aim to review the literature for the diagnosis and management of IPA, as well as present our IPA pathway, which we believe will reduce the difficulties clinicians may encounter when treating patients with IPA. Our three IPA cases are of colorectal, orthopaedic and urological origin. All patients underwent percutaneous drainage of the IPA, with one proceeding to open drainage. No mortalities were reported. IPA is a condition that presents diagnostic and therapeutic challenges to clinicians. The classical triad of IPA comprising of fever, abdominal/back pain and a limp is reported in just 5 – 30% of cases. Computed tomography remains the gold standard for diagnosis and radiologically guided drainage should be attempted in the first instance. The literature emphasizes the importance of maintaining a high index of suspicion for IPA, as it can be easily misdiagnosed within a wide range of differentials. Empirical treatment consists of broad-spectrum antibiotics, which should be adjusted when blood/aspirate cultures are available. Open drainage should be reserved for cases where percutaneous attempts are not appropriate, unsuccessful, or a patient clinically deteriorates. In a practical sense there is often confusion as to which specialties should best manage IPA. In recognising these difficulties, an IPA pathway would act as a concise guide for clinicians and ultimately optimise patient care.